Mitochondrial Electron Transport Chain Complex III Is Required for Antimycin A to Inhibit Autophagy - Ma, Xiuquan (2011)
Autophagy is a cellular lysosome-dependent catabolic mechanism mediating the turnover of intracellular organelles and long-lived proteins. Dysfunction of autophagy has been implicated in multiple human diseases. Identification of novel autophagy factors in mammalian cells is important for understanding how this complex cellular pathway responds to a broad range of challenges. Here we report that mitochondrial electron transport chain (mETC) complex III plays a role in autophagy induction. We show that antimycin A, a known inhibitor of mETC complex III, can inhibit autophagy. A structural and functional study shows that four close analogs of antimycin A that have no effect on mitochondria inhibition also do not inhibit autophagy; while myxothiazol, another mETC complex III inhibitor with unrelated structure to antimycin A, inhibits autophagy. Additionally, antimycin A and myxothiazol cannot inhibit autophagy in mtDNA-depleted H4 and mtDNA-depleted HeLa cells. These data suggest that antimycin A inhibits autophagy through its inhibitory activity on mETC complex III. Our data suggest that mETC complex III may have a role in mediating autophagy induction.